E-ServiceQuality Model and Kano Model: An Integration Improvement on Service Quality in E-Commerce Services - Krishna Kusumahadi; Widya Sastika; Fanni Husnul Hanifa (Research Synergy Foundation, 2022)
Indonesia has become the largest e-commerce market in South East Asia. According to Wearesocial and Hootsuite data, around 90% of internet users in Indonesia have experienced online shopping. In 2019, the e-commerce market's capital value in Indonesia reached USD 21 Million or about Rp 294 trillion. Based on McKinsey Report, the e-commerce industry in Indonesia is predicted to reach USD 40 million in 2022. The increase of online shopping activity reached 400% during the 2020 pandemic, causing a 23.11% increase in e-commerce service complaints. This research is conducted for improvement in e-commerce's service quality by integrating the kano model and E-ServiceQuality model. Results obtained from customers' needs will be true customer needs able to be analysed for the purpose of increasing satisfaction. Attributes of needs obtained from the voice of the customer will be grouped into E-ServiceQuality dimensions, such as Efficiency, Fulfilment, Reliability, privacy, responsiveness, compensation, and contact. Afterward, these attributes of needs will generate strong attributes and weak attributes grouped into several categories, kept, developed, and ignored. Based on the research conducted among 400 respondents, the conclusions to answer problems according to problem formulation within this research are obtained. The result of this classification is True Customer Needs, where the seven attributes are recommended to be improved, and one attribute is recommended to be developed. The eight attributes which become True Customer Needs are Interaction Channel, Customer Service Responsiveness, Website Feature, Up to Date Information, 24-hour Service, Quick Complaints Response, Cheap/Free Delivery Fee, and correct product guarantee.